NILAI KECANTIKAN PEREMPUAN DALAM PUISI AMINAH KARYA WS RENDRA - Rifari Baron (Jurnal Metamorfosa, 2020)
This study aimed to examine and discover the value of beauty for women through a poem entitled Aminah by WS. Rendra. Beauty was an important phenomenon for every woman. However, how this woman's concept become a good value for herself. This study used qualitative research with content analysis methods. Data were collected using fragments of poetry. Data analysis consisted of data reduction, data presentation, conclusion / verification. The results showed that the figure of Aminah had a beauty which was admired by all men or everyone in her village. Aminah became a village flower, but her figure had became a proud and arrogant woman. In her findings, Aminah's beauty had no value that given a positive impact on herself or the community. Aminah became a miserable person because of the greed that came from her beauty. She became a woman who fell into the valley of black life as a Commercial Sex Worker. At the end of the poem story, Aminah was to return as the nature of women despite having to face scolding from the community. So, the value of women's beauty must be balanced between physical, psychological, and social. Abstrak Penelitian ini bertujuan untuk mengkaji dan menemukan nilai kecantikan bagi perempuan melalui puisi berjudul Aminah karya WS. Rendra. Kecantikan menjadi fenomena penting bagi setiap perempuan. Namun, bagaimana konsep perempuan ini menjadi nilai yang baik bagi diri perempuan itu sendiri. Penelitian ini menggunakan penelitian kualitatif dengan metode analisis isi. Data dikumpulkan menggunakan penggalan puisi. Analisis data terdiri dari reduksi data, penyajian data, penarikan kesimpulan/verifikasi. Hasil penelitian menunjukkan bahwa sosok Aminah memiliki kecantikan yang sangat dikagumi oleh semua laki-laki ataupun semua orang di desanya. Aminah menjadi bunga desa, namun sosoknya telah menjadi perempuan yang sombong dan angkuh. Dalam temuannya kecantikan Aminah tidak memiliki nilai yang berdampak positif terhadap dirinya ataupun masyarakat. Aminah malah menjadi orang yang sengsara karena keserakahannya yang berasal dari kecantikannya. Dia menjadi perempuan yang terjerumus pada lembah kehidupan hitam sebagai Pekerja Komersial Seks. Pada akhir cerita puisi, Aminah ingin kembali pada fitrah perempuan walaupun harus menghadapi cacian dari masyarakat. Jadi, nilai kecantikan perempuan harus seimbang antara fisik, psikis, dan sosial. Kata Kunci: Aminah, Nilai Kecantikan, Perempuan, Puisi